Best interests, dementia and the Mental Capacity Act (2005). Issue 12 (30th November 2009) - Hope, T; Slowther, A; Eccles, J
Abstract : The Mental Capacity Act (2005) is an impressive piece of legislation that deserves serious ethical attention, but much of the commentary on the Act has focussed on its legal and practical implications rather than the underlying ethical concepts. This paper examines the approach that the Act takes to best interests. The Act does not provide an account of the underlying concept of best interests. Instead it lists factors that must be considered in determining best interests, and the Code of Practice to the Act states that this list is incomplete. This paper argues that this general approach is correct, contrary to some accounts of best interests. The checklist includes items that are unhelpful. Furthermore, neither the Act nor its Code of Practice provides sufficient guidance to carers faced with difficult decisions concerning best interests. This paper suggests ways in which the checklist can be developed and discusses cases that could be used in an updated Code of Practice.